Central Sumatra Basin: The First Sedimentary Basin for Geothermal Energy Development in Indonesia? (Rudarsko-geološko-naftni zbornik, 2025)
Indonesia heavily relies on the volcanic arc as an area for geothermal energy exploration and exploitation. Several Geothermal Power Plants (GPP) such as Sibayak (North Sumatra), Sarulla (North Sumatra), Salak (West Jawa), and Kamojang (West Java) use energy within the Quaternary volcanic arc region. However, alongside the Central Sumatra Basin (CSB), which exhibits strong heat flow, the construction of power plants clashes with socio-economic and environmental concerns. Therefore, this research aimed to use geothermal data from 326 oil wells in the CSB in order to better understand the geothermal and geological features, as well as the opportunities for energy development. The results showed that the outcropping rocks in the CSB have low to very high thermal conductivity (from 1.7 to over 2.1 W/m°C), as well as very high values of geothermal gradient (from 30 to over 120°C/km), and a heat flow ranging from 70 to >150 m/Wm2. As a result, the CSB became known across the world as the sedimentary basin with unusually strong heat flow. This elevated heat flow in the CSB originated from the upwelling asthenosphere, triggered by processes such as slab roll-back and pull-apart during the Tertiary age. The processes led to a significantly thin crustal thickness of 27 km in the CSB, along with the formation of normal faults. Comparative analysis with other basins worldwide underscored the enormous potential for geothermal exploitation within the CSB. This research was expected to redirect the focus of geothermal energy adoption towards the CSB, to minimize social and environmental effects while striving for zero emissions by 2060.